Employee Wellbeing sebagai Kunci Sukses Merger dan Akuisisi: Analisis Pengalaman Karyawan Pasca-Akuisisi PT Bank Syariah Indonesia - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Mergers and acquisitions (M&A) often fail to achieve strategic goals due to a lack of attention to human factors, particularly employee well-being. This qualitative research analyzes the experiences of PT Bank Syariah Indonesia (BSI) employees post-merger of three Islamic banks in 2021, focusing on the impact of M&A on employee wellbeing and coping strategies. Data were collected through in-depth interviews with 15 employees from various levels and analyzed using a thematic approach. The research findings revealed that: (1) workload increased significantly post-merger, causing physical exhaustion and psychological stress; (2) career uncertainty and changes in organizational culture were the main sources of anxiety; however, (3) shared sharia values acted as cultural glue; and (4) wellbeing programs such as counseling and work flexibility proved effective in improving employee adaptation. This study contributes to the literature by showing that an employee well-being-based approach that integrates physical, mental, and spiritual aspects is the key to successful M&A in the Islamic banking industry. The practical implications emphasize the need for transparent communication, structured psychological support, and harmonization of shared value-based culture in the post-M&A integration process.